Ecological Validity of the Yo-Yo SFIE2 Test - Krustrup, P.; Randers, M.; Horton, J.; Brito, J.; Rebelo, A. (International Journal of Sports Medicine, 2012)
The present study investigated the movement pattern of Portuguese top-level futsal referees (n=16) during competitive games and the ecological validity of the new Yo-Yo Sideways-Forwards Intermittent Endurance level 2 test (Yo-Yo SFIE2). Total distance covered (TD), high-intensity running (HIR), sprinting (SPR), and sideways running (Sw) during matches were 5.78±0.24 (±SEM), 0.77±0.08, 0.17±0.02 and 1.61±0.28 km, respectively, with peak 5-min values of 0.50±0.02, 0.12±0.01, 0.05±0.01 and 0.20±0.02 km, respectively. TD, HIR and Sw decreased by 30% (p<0.001), 43% and 60% (p<0.01), respectively from the first to the last 10-min period. Yo-Yo SFIE2 performance was 1205±107 (625–2015) m and showed large correlations with match-values and peak 5-min values for HIR (r=0.58 and 0.68, p<0.01) and SPR (r=0.56 and 0.57, p<0.05). Yo-Yo SFIE2 HR after 4 min [95±1 (87–99) % HRpeak] showed a nearly perfect inverse correlation with Yo-Yo SFIE2 performance (r=− 0.90, p<0.001) and large inverse correlations (p<0.05) with match-values and peak 5-min values for HIR (r=− 0.55 and − 0.71) and SPR (r= − 0.57 and  − 0.55). In conclusion, the Yo-Yo SFIE2 test is movement-specific for top-level futsal referees as high-intensity running and sideways running are important parts of their match activity profile, and maximal and sub-maximal versions of the Yo-Yo SFIE2 test correlates with certain aspects of the physical match performance of top-level futsal referees.
Keywords: time-motion analysis; heart rate; sideways running; high-intensity running; maximal testing; sub-maximal testing; assistant referee intermittent endurance test (ARIET)